Clinical Characteristics and Comorbidities Associated With COVID-19 Deaths in Brebes Regency (Retrospective Cohort Study) - Diah Hasanah; Lukman Fauzi (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2023)
Background: Until now, COVID-19 is still a major global health problem. Even though Brebes Regency is not the regency with the highest number of COVID-19 cases in Central Java, Brebes Regency has not been spared from a spike in COVID-19 cases. The active case of COVID-19 in Brebes Regency in 2021 is 0.43% with a CFR of 10.98%. It is proven that active cases of COVID-19 have increased from the previous year which was only 0.05%. This research aimed to determine the factors associated with COVID-19 deaths in Brebes Regency. Method: The study design was a retrospective cohort using secondary data from Brebes Regency Health Office 2021. This research was conducted in September-November 2022. The number of samples studied was 10,374 samples. Data were analyzed using univariate, bivariate (chi-square and fisher), and multivariate (logistic regression) analysis. Results: The results showed that age ≥50 years (OR: 3.74; 95% CI: 3.28-4.26), symptoms of shortness of breath (OR: 2.84; 95% CI: 2.42-3, 34), heart disease (OR: 3.21; 95% CI: 1.29-7.99) and type of work as a health worker (OR: 0.30; 95% CI: 0.09-0.97) have significant relationship to the death of COVID-19 patients in Brebes Regency. Conclusion: Age ≥50, symptoms of shortness of breath, heart disease and type of work as a health worker increase the risk of death in COVID-19 patients in Brebes Regency.